Peningkatan Keterampilan Memerankan Tokoh dengan Menggunakan Metode Sosiodrama Siswa Sekolah Dasar - Selviana Sasmiati Nur; Masrul Masrul; Nurmalina Nurmalina (Journal on Education, 2022)
The background of the research is the low achievement of learning Indonesian in drama material for fifth grade students at Pahlawan Elementary School, Bangkinang District, Kampar Regency, Riau. The low results of learning to play drama because students are not trained by teachers in playing drama characters, so students experience difficulties in acting out drama with proper pronunciation, intonation, expression, and appreciation. Learning with the sociodrama method was chosen, because in addition to training students' courage to play drama, it also makes students active in learning and develops cooperation within students. The purpose of this study was to improve the skills of playing drama characters in fifth grade students of SD Pahlawan. The subjects in the study were teachers and fifth grade students at SD Pahlawan, Bangkinang District, Kampar Regency, Riau. The number of students is 17 children, consisting of 7 male students and 10 female students. This research is a Classroom Action Research (CAR). Data collection methods used are tests, observations, and documentation. Prior to conducting the research, the researcher conducted preliminary observation activities through interviews. The data analysis technique in this study is quantitative descriptive statistics, namely by finding the average. The results showed that learning the skills of playing drama characters using the sociodrama method could improve the skills of playing the characters of the fifth grade students of SD Pahlawan. Class average results in cycle I average student score of 67.47 with classical completeness of 70.58% (11 students). In cycle II, the average score of students increased again to 77 with a classical mastery level of 88.23% (15 students). From the data obtained, it can be concluded that the sociodrama method can improve learning outcomes and student activity in drama material.